Effect of NaOH on biogas production under SSAD conditions along with kinetics studies - Hashfi Hawali Abdul Matin; Hadiyanto Hadiyanto (School of Postgraduate Studies, Diponegoro Univer, 2020)
Indonesia is a large rice producing country where from these activities it produces waste in the form of rice husk. Rice husk cannot be degraded by itself due to the lignin content contained in the rice husk. Therefore, treatment is carried out to destroy the lignin content and use it as alternative energy in the form of biogas. The study was conducted at a laboratory scale at room temperature, preliminary treatment using 3% NaOH under the SSAD conditions of 27.5% TS and then biogas production was measured once every two days for 90 days. Furthermore, the results of biogas production were observed between biogas with NaOH and without NaOH and carried out a study of the kinetics. The result is that biogas production with NaOH is higher, reaching 59.2 mL/grTS whereas without NaOH at 14.7 mL/grTS. The results of kinetic studies using mathematical modeling through the Gompertz equation, the variable with NaOH is known to have a maximum biogas production of 63.9 mL/grTS, a daily biogas production rate of 0.97 mL/grTS.day and the initial formation of biogas significantly on the 8th day.